New technologies provide innovative opportunities to enhance understanding of major virus diseases threatening global food security - Kreuze, Jan F.; Cuéllar, Wilmer Jose; Kumar, P. Lava; Prasanna, Boddupalli M.; Omondi, Bonaventure Aman Oduor (American Phytopathological Society, 2023)
Plant viruses pose a continuous and serious threat to crop production worldwide, while globalization and climate change are exacerbating the establishment and rapid spread of new viruses. Simultaneously, developments in genome sequencing technology, nucleic acid amplification methods, and epidemiological modeling are providing plant health specialists with unprecedented opportunities to confront these major threats to the food security and livelihoods of millions of resource-constrained smallholders. In this perspective, we have used recent examples of integrated application of these technologies to enhance understanding of the emergence of plant viral diseases of key food security crops in low- and middle-income countries. We highlight how international funding and collaboration have enabled high-throughput sequencing-based surveillance approaches, targeted field and lab-based diagnostic tools, and modeling approaches that can be effectively used to support surveillance and preparedness against existing and emerging plant viral threats. The importance of national and international collaboration and the future role of CGIAR in further supporting these efforts, including building capabilities to make optimal use of these technologies in low- and middle-income countries is discussed.